The Pattern of Physics Education Students’ Diagrams and Answers in Solving Force Problems - J. Sirait; J. Ainley; M. Barstow (Jurnal Pendidikan IPA Indonesia, 2023)
Force diagrams or some say free body diagrams (FBDs), as physics representations, are usually employed to teach and learn physics concepts such as force. Physics education studies indicate that the use of FBDs can support or hinder students’ performance in solving physics problems. This study aims to investigate the type of representations drawn by students and the patterns of students’ answers while solving force problems. By involving 230 preservice physics teachers, questions about the application of Newton’s laws were administered to students to elicit the patterns of students’ diagrams and answers. Results were analysed into three categories: complete, incomplete, and inappropriate force diagrams. In addition, some students did not draw diagrams in solving the problems. Based on students’ answers, the percentage of students drawing incomplete diagrams (54% for horizontal problems and 42% for inclined problems) is higher than drawing complete diagrams (18% for horizontal problems and 35% for inclined problems). The percentage of students who drew inappropriate diagrams in solving horizontal and inclined problems is 20% and 10%, respectively. A few students (8% and 13%) did not draw diagrams for both questions. Students who drew complete diagrams tended to obtain the correct final answer. Some students who drew incomplete diagrams were not able to find the correct answers and even finish the problem. However, some students who drew incomplete diagrams could successfully solve the problem. The group of students who drew diagrams in the inappropriate category tended to demonstrate incorrect and unfinished answers. This study suggests that instructors should not only focus on the correctness of the diagrams but also focus on the completeness of diagrams drawn by students while solving the problems.